Acute and Severe Acute Pancreatitis and the Effect of Cannabis in States Before and After Legalization Compared With States Without Legalized Cannabis. Issue 5 (May 2021) - Lara, Luis F.; Nemer, Laura; Hinton, Alice; Balasubramanian, Gokulakrishnan; Conwell, Darwin L.; Krishna, Somashekar
Abstract : Objectives: Cannabis legalization has increased its use. The incidence of acute pancreatitis (AP) and severe acute pancreatitis (SAP) has also increased. In this study, data on pancreatitis were obtained from 2 states before and after cannabis legalization and compared with 2 states without legalized cannabis. Methods: Data were extracted from State Inpatient Databases from the states of Colorado and Washington before recreational cannabis legalization (2011) and after legalization (2015). Arizona and Florida were used as the nonlegalized cannabis states. Multivariable logistic regression models were fit for AP and SAP to determine a trend difference between legalized and nonlegalized cannabis states. Results: Cannabis use, AP, and SAP increased in all states. The increase in AP and SAP was not significantly different between the states that legalized cannabis use and those that did not. Legalized cannabis states had lower charges for AP and SAP and shorter length of hospitalizations. Conclusions: The trend of AP and SAP increased during the study period, but this was not correlated to cannabis use. Cannabis users had lower hospitalization costs and hospital stay. The effects of other confounders such as cannabis dose and delivery methods, alcohol, tobacco, and others need to be studied further as use increases. Abstract : Supplemental digital content is available in the text.